Comparisons in Muscle Function and Training Rehabilitation Outcomes Between Avoidance-Endurance Model Subgroups. Issue 10 (October 2017) - Fehrmann, Elisabeth; Tuechler, Kerstin; Kienbacher, Thomas; Mair, Patrick; Spreitzer, Juliane; Fischer, Linda; Kollmitzer, Josef; Ebenbichler, Gerold
Abstract : Objectives: Evidence suggests that chronic low back pain patients with fear-avoidance (FAR) or endurance behavior are at risk of treatment failure and pain maintenance, with bodily overuse or underuse being assumed as mediating mechanisms for pain chronification. This study sought to examine whether or not the avoidance-endurance model subgroups, FAR, distress-endurers (DER), eustress-endurers (EER), and adaptive responders (AR), differed in physical measures and outcomes after training therapy. Materials and Methods: A total of 137 chronic low back pain patients were assessed before, at the end of, and 6 months after a 6-month rehabilitation training. Patients performed maximum back extension strength and trunk range-of-motion measures, flexion-relaxation tests, and completed the following questionnaires: Avoidance-Endurance Questionnaire, Roland-Morris Disability Questionnaire, Pain Disability Index, 36-Item Short-Form Health Survey, International Physical Activity Questionnaire, and visual analog scale. Statistical analysis included cluster analysis, analysis of covariances, and mixed-effects models. Results: At baseline, avoidance-endurance model subgroups did not differ in physical measures and activity levels. At the end of training, patients' back-related health was significantly improved in all subgroups. However, the DER and the FAR were found to be more impaired before and after the intervention compared with EER and AR, as indicated by a higher pain intensity, higher disability levels, lower quality of life, and inferior working capacity. Discussion: Although FAR and DER did not differ in physical measures or activity levels from EER and AR, they demonstrated poor lower back-related health at baseline and after intervention. Thus, future research should elucidate as to which additional interventions could optimize their health.